Neoliberal redistributive policy: The U.S. net social wage in the 21st century - Katherine A. Moos (University of Massachusetts, Department of Economics, 2017)
In this paper, I examine the trends of fiscal transfers between the state and workers during 1959 - 2012 to understand the net impact of redistributive policy in the United States. This paper presents original net social wage data from and analysis based on the replication and extension of Shaikh and Tonak (2002). The paper investigates the appearance of a post-2001 variation in the net social wage data. The positive net social wage in the 21st century is the result of a combination of factors including the growth of income support, healthcare inflation, neoliberal tax reforms, and macroeconomic instability. Growing economic inequality does not appear to alter the results of the net social wage methodology.
Keywords: H5; E62; E64; B5; 330; fiscal policy; net social wage; neoliberalism; social spending; taxation